Investigation of machining coolant residue cleaning methods for Ti6Al4V part fabrication through hybrid manufacturing process. (April 2018) - Yan, Lei; Zhang, Yunlu; Newkirk, Joseph W.; Liou, Frank; Thomas, Eric; Baker, Andrew
Abstract: A major concern in the hybrid manufacturing of Ti-6Al-4V parts is whether coolant residue from wet machining will cause contamination subsequent laser metal deposition operations. Laser rastering and compressed air were used in a cleaning effectiveness study with oil- and water-based coolant residue. The cleaning effect was evaluated by Vickers hardness and tensile tests on parts which were built on cleaned surfaces by the aforementioned methods. The conclusions, drawn from comparison with deposit built on dry machining surface, indicates laser heating for thin oil-based coolant residue and laser heating then cleaning with compressed air for water-based coolant residue yield good cleaning effectiveness.